2021
DOI: 10.1155/2021/7088856
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Effects of Suicidal Ideation and Childhood Abuse on Brain Structure and Function in Major Depressive Disorder Patients

Abstract: Suicidal ideation (SI) is a direct risk factor for suicide in patients with depression. Regarding the emergence of SI, previous studies have discovered many risk factors, including childhood abuse as the major public problem. Previous imaging studies have demonstrated that SI or childhood abuse has effects on brain structure and function, respectively, but the interaction effects between them have not been fully studied. To explore the interaction effect between SI and childhood abuse, 215 patients with major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…A total of 295 records were identified through database searches. Forty-five studies were eligible for inclusion, of which eight were CTh studies based on SBM (Bounoua, Miglin, Spielberg, & Sadeh, 2020; Cascino et al, 2022; Corbo et al, 2014; Jaworska et al, 2014; Kelly et al, 2013, 2016; Lim et al, 2018; Ross et al, 2021), 34 were GMV studies based on VBM (Benedetti et al, 2012; Brito et al, 2013; Carballedo et al, 2012; Carrion et al, 2009; Chaney et al, 2014; Dam, Rando, Potenza, Tuit, & Sinha, 2014; Daniels et al, 2019; Duarte et al, 2016; Everaerd et al, 2016; Fan et al, 2022; Grabe et al, 2016; Harmelen et al, 2010; Kelly et al, 2015; Kuhn et al, 2016; Labudda et al, 2013; Liao et al, 2013; Lu et al, 2013, 2018, 2019; Maier et al, 2020; Mielke et al, 2016, 2018; Opel et al, 2016, 2019; Rinne-Albers et al, 2017; Sheffield, Williams, Woodward, & Heckers, 2013; Thomaes et al, 2010; Tomoda et al, 2009a, 2009b, 2011; Tomoda, Polcari, Anderson, & Teicher, 2012; Walsh et al, 2014; Wang et al, 2021; Yang et al, 2017), and 3 conducted both SBM and VBM analyses (Gao et al, 2022; Lim & Khor, 2022; Rinne-Albers et al, 2020). Among the VBM studies, two study both included two subgroups (Carballedo et al, 2012; Everaerd et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 295 records were identified through database searches. Forty-five studies were eligible for inclusion, of which eight were CTh studies based on SBM (Bounoua, Miglin, Spielberg, & Sadeh, 2020; Cascino et al, 2022; Corbo et al, 2014; Jaworska et al, 2014; Kelly et al, 2013, 2016; Lim et al, 2018; Ross et al, 2021), 34 were GMV studies based on VBM (Benedetti et al, 2012; Brito et al, 2013; Carballedo et al, 2012; Carrion et al, 2009; Chaney et al, 2014; Dam, Rando, Potenza, Tuit, & Sinha, 2014; Daniels et al, 2019; Duarte et al, 2016; Everaerd et al, 2016; Fan et al, 2022; Grabe et al, 2016; Harmelen et al, 2010; Kelly et al, 2015; Kuhn et al, 2016; Labudda et al, 2013; Liao et al, 2013; Lu et al, 2013, 2018, 2019; Maier et al, 2020; Mielke et al, 2016, 2018; Opel et al, 2016, 2019; Rinne-Albers et al, 2017; Sheffield, Williams, Woodward, & Heckers, 2013; Thomaes et al, 2010; Tomoda et al, 2009a, 2009b, 2011; Tomoda, Polcari, Anderson, & Teicher, 2012; Walsh et al, 2014; Wang et al, 2021; Yang et al, 2017), and 3 conducted both SBM and VBM analyses (Gao et al, 2022; Lim & Khor, 2022; Rinne-Albers et al, 2020). Among the VBM studies, two study both included two subgroups (Carballedo et al, 2012; Everaerd et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the small number of studies on MDD + S populations and the negative results, we discussed the relationship of SI with GMV and IL-6, expecting to find some evidence. Changes of GMVs in several cortical and subcortical structures were linked to SI ( Wang et al, 2021 ). Besides, the decreased GMVs of dorsal striatum predicted self-associations with death, namely the implicit SI ( Ho et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many findings about the impaired gray matter volumes (GMVs) in MDD + S have been reported. For example, previous studies had shown that the reductions of GMVs in the bilateral caudate nucleus, right nucleus accumbens ( Ho et al, 2021 ), dorsal striatum ( Ho et al, 2018 ), the lingual gyrus ( Wang et al, 2021 ), right insula ( Ge et al, 2021 ), bilateral dorsolateral prefrontal cortex and right ventrolateral prefrontal cortex ( Zhang et al, 2020 ) were related to SI in MDD patients. In addition, gray matter thickness, an indicator related to GMVs, also found a specific change in MDD + S. For example, Taylor.…”
Section: Introductionmentioning
confidence: 99%
“…All resting-state fMRI (rs-fMRI) scans were performed with a 3.0T General Electric scanner at the PET center of Renmin Hospital of Wuhan University using previously described methods ( 31 ). Briefly, participants were directed to lie in the supine position with their eyes closed while remaining awake and motionless.…”
Section: Methodsmentioning
confidence: 99%